Bats in the Anthropocene: Conservation of Bats in a Changing World 2015
DOI: 10.1007/978-3-319-25220-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Insectivorous Bats and Silviculture: Balancing Timber Production and Bat Conservation

Abstract: Forests are one of the most important habitats for insectivorous bats as they offer the potential for both roosting and foraging. We reviewed silvicultural literature from North America, Australia, and Europe and found that diverse research approaches have revealed commonalities in bat responses to forest silviculture. Almost all silvicultural treatments evaluated were compatible with some use by forest bats, though different bat ensembles respond in different ways. Ensemble ecomorphology was a consistent pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 166 publications
(188 reference statements)
0
58
0
Order By: Relevance
“…The importance of retaining dead trees as roosts for bats, even those that are relatively small (~20 cm DBH), is a further clear management action emerging from our study (see also [5]). Unexpectedly, we also identified ring-barking as an important contributor to the abundance of dead trees in our study area.…”
Section: Management Implicationsmentioning
confidence: 78%
See 4 more Smart Citations
“…The importance of retaining dead trees as roosts for bats, even those that are relatively small (~20 cm DBH), is a further clear management action emerging from our study (see also [5]). Unexpectedly, we also identified ring-barking as an important contributor to the abundance of dead trees in our study area.…”
Section: Management Implicationsmentioning
confidence: 78%
“…This species is widely distributed across a range of habitats, including semi-cleared farmland in south-eastern Australia. Considerably more data are needed on the patterns of roost selection by different bat species in relation to different management treatments [5]. We are aware of just one other study of bat roosts in relation to thinning, which found a less manoeuvrable edge-space species (Lasiurus borealis) roosting in open conditions created by thinning [29].…”
Section: Roost Selectionmentioning
confidence: 99%
See 3 more Smart Citations